Incidental Adrenocortical Carcinoma in Dogs: Clinical, Tomographic and Histopathological - Pelegrini, Náthalye Fernandes; Gomes Lima, Helen Cristina; Burema, Mayara da Cruz; dos Santos, Tarcísio Ávila; Néspoli, Pedro Eduardo Brandini; Ribeiro, Alexandre Pinto; Moleta, Edson Colodel; Franco Sousa, Valéria Regio (Acta Scientiae Veterinariae, 2019)
Background: Adrenal incidentalomas are masses accidentally discovered during imaging examinations performed when there is no suspicion of adrenal disease. Even with a low prevalence, it is important to perform a reliable evaluation observing biological behavior and determining whether the hormonal activity is stimulated. Frequently, these masses are not functional, but in some cases, there is increased cortisol activity, and patients with adrenal incidentalomas may present hyperadrenocorticism. This report aims to describe the clinical, tomographic, and histopathological aspects of a case of adrenal incidentaloma detected in a routine abdominal ultrasound. Case: An 8-year-old, male, maltese dog with occasional emesis, halitosis, claudication of the left pelvic limb, and previous compensated and untreated cardiomyopathy was treated at the Veterinary Hospital of the Federal University of Mato Grosso (HOVET-UFMT). Physical examination revealed arterial hypertension and claudication, with the positive posterior drawer test suggesting rupture of the cruciate ligament. The blood count showed no alteration, and the serum biochemistry revealed a slight increase in the activity of alanine aminotransferase. In order to investigate this increase, an abdominal ultrasound was performed. Slight hepatomegaly and a heterogeneous mass of irregular edges were observed with a moderate and difficult-to-delimit vascularization of the adrenal gland. Left knee radiography raised the suspicion of rupture of the cranial cruciate ligament due to the cranial displacement of the tibia in relation to the femur. Computed tomography was performed to define the extent and delimitation of the mass, which was compatible with a tumor of the right adrenal gland characterized by the visualization of an abdominal mass between the kidneys, extending from the hepatic region to the cranial pole of the left kidney. On follow-up, the patient was reported to have diarrhea with black stools, and a low-dose dexamethasone suppression test was ordered. Unilateral adrenalectomy was recommended due to the suspicion of pheochromocytoma. During the surgical procedure, the mass adhered to the abdominal wall and the diaphragm resulting in the death of the animal. Histopathological analysis revealed a cellular proliferation of cortical adrenal cells forming multiple cell nests separated by a small amount of fibrovascular stroma. Proliferated cells were polyhedral, with densely eosinophilic cytoplasm and well-defined edges, and were occasionally vesicular. They had globular nuclei, slightly stained chromatin, and inconspicuous nucleoli. Pleomorphism, anisocytosis, and anisokaryosis were accentuated, and eight mitosis figures were observed in ten high-power fields (40×), leading to a diagnosis of adrenocortical carcinoma. Discussion: When there is no suspicion or characteristic clinical sign, and adrenal growth is observed on imaging examination, the finding may be called an incidentaloma. Here, the incidentaloma was a non-functional adrenal carcinoma, because the tests were not conclusive. Adrenal carcinomas grow by infiltrating adjacent tissues, such as the caudal vena cava. In this case, it infiltrated the abdominal wall and diaphragm. Therefore, imaging, ultrasound, and tomography examinations were important for the characterization of the adrenal incidentaloma in this dog. This adrenal incidentaloma, which was a carcinoma with metastasis to the adjacent tissues, required other hormonal tests to rule out further endocrine dysfunctions.